2022
DOI: 10.1177/00405175211068369
|View full text |Cite
|
Sign up to set email alerts
|

Novel germanium-polyamide6 fibers with negative air ions release and far-infrared radiation as well as antibacterial property

Abstract: There has been much concern about germanium because of its special atomic nuclear structure to generate negative electrons and far-infrared ray. In this study, novel germanium-polyamide6 fibers were prepared by using micro–nano structured germanium particles as a functional component via melt spinning. The effects of germanium concentration on the morphology, mechanical, negative air ion-releasing, and far-infrared radiation properties of the germanium-polyamide6 fibers were systematically investigated. Beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In our previous work, we prepared germanium–polyamide 6 (Ge-PA6) composite fibers and discussed their NAI release and far-infrared radiation properties to investigate the feasibility of their application in fiber manufacture. 19 Our results demonstrated that NAI production was affected by the ionization degree of air molecules and the extranuclear electron activity of germanium, which was related to germanium particle size. Therefore, in this work, three types of Ge-PA6 fibers using three kinds of germanium particles with different sizes were prepared, and the effect of germanium particle size on the morphologies, mechanical properties, NAI release and antimicrobial efficiencies of the fibers were systematically analyzed.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…In our previous work, we prepared germanium–polyamide 6 (Ge-PA6) composite fibers and discussed their NAI release and far-infrared radiation properties to investigate the feasibility of their application in fiber manufacture. 19 Our results demonstrated that NAI production was affected by the ionization degree of air molecules and the extranuclear electron activity of germanium, which was related to germanium particle size. Therefore, in this work, three types of Ge-PA6 fibers using three kinds of germanium particles with different sizes were prepared, and the effect of germanium particle size on the morphologies, mechanical properties, NAI release and antimicrobial efficiencies of the fibers were systematically analyzed.…”
mentioning
confidence: 58%
“…The NAI production was analyzed using a self-assembled double-drum testing apparatus equipped with a NAI recorder, which was the same as that used in our previous work. 19 The fiber samples were woven into a knitted fabric with a size of 20 cm × 5 cm and analyzed at different temperatures and extrusion forces. The measurement was repeated three times and then averaged to get the NAI production value (the detailed measurement is given in the supplementary material).…”
Section: Methodsmentioning
confidence: 99%
“…Negative air ions (NAI) exert unique effects on the human body, such as sterilization, air freshening, and functional balance regulation, and are acclaimed as "vitamins and growth factors" in the air [1][2][3]. In an environmental evaluation system, the NAI concentration is a crucial indicator for assessing air quality [4]. However, in recent years, with the excessive exploitation and irrational utilization of natural plant resources by human beings, the NAI concentration around our bodies is getting lower and lower [5], which poses a significant threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Ding 19 used tourmaline powder as an additive and two-dipping and two-rolling process to develop functional cotton knitted products, it was found that the particle size of tourmaline powder is an important factor in its negative ion emission, smaller powders are more evenly distributed on the fabric and emit more negative ions. Chen et al 20 combined micro- and nanostructured germanium particles with polyamide to produce new germanium-polyamide six fibers with good negative ion release and far-infrared radiation properties as well as antibacterial properties by melt spinning. These research results provide useful references for the far-infrared functional finishing of fabrics.…”
Section: Introductionmentioning
confidence: 99%